2011
DOI: 10.1016/j.drugalcdep.2010.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Resisting temptation: Decreasing alcohol-related affect and drinking behavior by training response inhibition

Abstract: According to dual-process models, excessive alcohol use emerges when response inhibition ability is insufficient to inhibit automatic impulses to drink alcohol. This study examined whether strengthening response inhibition for alcohol-related cues decreases alcohol intake. Fifty-two heavy drinking students were randomly assigned to one of two conditions: In the beer/no-go condition, participants performed a go/no-go task that consistently paired alcohol-related stimuli with a stopping response, to increase res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

18
329
9
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 359 publications
(360 citation statements)
references
References 26 publications
(34 reference statements)
18
329
9
4
Order By: Relevance
“…Alternatively, interventions that directly target self-control, at either the trait or alcohol-specifi c level, may be fruitful in directly affecting drinking or affecting the infl uence of implicit processes on drinking. Supporting this notion, a recent study revealed that a working memory training task increased control over automatic alcohol-related impulses in problem drinkers and resulted in reduced alcohol intake up to 1 month after training (Houben et al, 2011a). Research also supports targeting alcohol-specifi c self-control as a potential intervention; for example, fi ndings from another study found that strengthening response inhibition for alcohol cues reduced weekly alcohol intake in heavy drinking students (Houben et al, 2011b).…”
Section: Discussionmentioning
confidence: 94%
“…Alternatively, interventions that directly target self-control, at either the trait or alcohol-specifi c level, may be fruitful in directly affecting drinking or affecting the infl uence of implicit processes on drinking. Supporting this notion, a recent study revealed that a working memory training task increased control over automatic alcohol-related impulses in problem drinkers and resulted in reduced alcohol intake up to 1 month after training (Houben et al, 2011a). Research also supports targeting alcohol-specifi c self-control as a potential intervention; for example, fi ndings from another study found that strengthening response inhibition for alcohol cues reduced weekly alcohol intake in heavy drinking students (Houben et al, 2011b).…”
Section: Discussionmentioning
confidence: 94%
“…Concerning these interventions, the reviewed articles demonstrated that the evaluative conditioning, the Alcohol Approach Avoidance Task, the Alcohol Attention Control Training Program and the Motivational Interview of Miller and Rollnick (2002) are suitable procedures to modify IAC. Also, even though the Expectancy Challenge and the Go/No-go procedure constitute promising procedures for IAC modification, further studies should be conducted, since, as yet, results have been either contradictory (Houben et al, 2012;Houben et al, 2011) or dependent on methodological issues, such as on the algorithm used for IAT scoring (Wiers et al, 2005). Finally, one article (Ostafin & Palfai, 2012) underlined the importance of considering the possible effects of IAC on brief interventions aimed to reduce alcohol consumption.…”
Section: Discussionmentioning
confidence: 99%
“…On one hand, some of them indicated changes on implicit alcohol associations and diminished consumption (Houben, Havermans, Nederkoorn & Jansen, 2012;Houben et al, 2011). On the other hand, other article found reduction of consumption without changes in implicit alcohol associations (Bowley, Faricy, Hegarty, Johnstone, Smith, Kelly & Rushby, 2013).…”
Section: Topic 4: Interventions For Iacmentioning
confidence: 99%
See 2 more Smart Citations